Predisposing Factors and Etiology of Deep Neck Space Infections – A Hospital-based Cross-sectional Study - Utkarsh Jain; Mahima Luthra; Sampan Singh Bist; Lovneesh Kumar; Vinish Kumar Agarwal (Journal of Public Health and Primary Care)
Background: Deep neck space infections (DNSI) are serious infections of the potential spaces of the neck. In developing countries, dental infections have been found to be the most common cause of these infections. The signs and symptoms depend on the neck space involved. Timely surgical drainage remains the main mode of treatment. This study aims to determine the predisposing factors and etiology responsible for these infections. Materials and Methods: This cross-sectional study of 1 year was conducted in a tertiary care teaching hospital setting and included 52 cases of clinically diagnosed DNSI. The clinico-demographic profile, microbiological profile, predisposing factors, and etiology of DNSI were recorded in all patients and analyzed. Results: The mean age was 43.46 ± 18.07 years. The male-to-female ratio was 1.7:1. The most common presenting complaint was cervicofacial/oropharyngeal swelling (100%). The most frequently involved neck space was submandibular space (56%). Poor oral hygiene (78.8%), anemia (65.3%), and diabetes mellitus (55.7%) were the common predisposing factors, respectively. Streptococcus group of organisms were found in majority of the cases (19%) and cephalosporin was the most sensitive drug (100%). Dental infection was observed as the most common etiological cause (67.3%). Conclusion: Primary health-care physician should be aware of the signs and symptoms of DNSI so that early detection and timely referral can be done to prevent life threatening complications. Regular health and dental checkups should be encouraged for decreasing the incidence of these infections.